PAUL AT ATHENS: FRESH INSIGHTS - William Edgar (STTRII, 2020)
This paper discusses the challenges of Christian principles to adapt biblical message to today. It start with the growing trend toward individualism, and privatization of religion, violence and finally persecution. I will analyze the apologetics method in the famous speech given by the apostle Paul on Mars Hill, recorded in Acts 17:16-34. Then, finally making proposals on how Paul's approach to be used in the practice of today's Christian apologetics based on the challenges given above. KEYWORDS: Paul, privatization, faith, religion, apologetics, individualism.